THE RELATIONSHIP BETWEEN OUTDOOR MEDIA ADVERTISING, COUNSELING FOR COUNSELING TEACHERS, AND PEERS ON SMOKING BEHAVIOR AMONG STUDENTS AT STATE VOCATIONAL SCHOOL - 0marisa_oktavi4, Marisa (Indonesia Epidemiological Journal, 2024)
ABSTRACT Background: Smoking is still one of the biggest health problems. This habit is a risk to global health and can cause human death. Apart from that, smoking can also result in other health risks related to chronic diseases such as heart attacks, strokes, chronic obstructive pulmonary disease, emphysema, and cancer.This researcher aims to determine the relationship between outdoor media advertising and counseling from tutors and peers on smoking behavior among students at SMK Negeri 3 Oku in 2023. Method: This research design uses observational analytical research with a cross-sectional approach where data for both variables are collected at the same time. or at one time.In this research, the researcher will look for the relationship between outdoor media advertising, guidance counselors, and peer counseling on smoking behavior among students at SMK Negeri 3 Oku East Baturaja in 2023, totaling 876 students, so the sample size used in this study uses a finite sample size formula of 86.65 (rounded to 87) respondents. The statistical test used is the chi-square test.Results: The results of the bivariate analysis show that there is a significant relationship between outdoor media advertising and smoking behavior with a p value of 0.001, a significant relationship between counseling teacher counseling and smoking behavior with a p value of 0.000, and a significant relationship between peers and smoking behavior with a p value of 0.000. Conclusion: There is a significant influence on outdoor media advertising. Counseling guidance counselors and peers with smoking behavior.